The carbocidecis in height and functional pathology of the lung - Villagarcía, Víctor (1935)
The study of lung functionalism is a matter which, without good reason, has been long forgotten. As for other organs rapidly charged functional study, characters of real importance for the lung, however, it just outlined. And this is how you could say with Roger, the physiology of the lung was in the same state as it was the physiology of the liver before work Claudio Bernard, no one would give importance to what, indeed, has law.